DANCE AND PHYSICAL EDUCATION IN PERIODICALS PUBLISHED BETWEEN 1990 AND 2010 (Fiep Bulletin - online, 2012)
The work makes an effort to map the studies on the inclusion of dance in Physical Education, approaching the historical theoretical debate that marked his field from the 1990s. The analysis documentary corpus, covering the period 1990 to 2010, consists of 25 articles published in periodicals of expressiveness of Physical Education, cataloged by Proteoria group of Physical Education Center at Federal University of Espírito Santo, and articles published in CAPES periodicals database, available on the Internet. It concluded that despite the progress achieved with regard to the inclusion of dance in Physical Education classes, this content is still marginalized. In contrast, Brazilian theoretical production is presenting resolution proposals to problems that consider impede the full involvement of the dance at school, suggesting that efforts should go beyond the theoretical limits and into schools and universities.
Keywords: dance; Physical Education; academic production.